RANCANG BANGUN APLIKASI PENJUALAN PLYWOOD PADA PT SARI TANI PERKAYUAN INDONESIA - Sadewo, ferdyo Arie; sulistiowati, sulistiowati; churniawan, agus dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2019)
PT Sari Tani Perkayuan Indonesia is a company engaged in plywood sales, PT Sari Tani Perkayuan Indonesia sells Plywood made from logs of sengon and meranti type. The company sells ten products and each product has five types of grade, so far the business process in sales activities is done by way of customers coming directly to the company or contacting by telephone so that it can take the customer's time to find out the products sold by the company. The development of information technology has brought great changes in the business world. With the internet business can be done anytime and anywhere, one part of the development of technology is E-Commerce, which is an electronic trade that can help companies to introduce their products and can help companies to sell their products online. So far, PT Sari Tani Perkayuan Indonesia has not used E-Commerce facilities so that companies to introduce their products to the sales department come to property developers or furniture entrepreneurs to offer their products. With the existence of E-Commerce, it is expected to make it easier for companies to introduce their products and make it easier for customers to know the products sold by the company and can make purchases online without having to go to the company.